2002
DOI: 10.1001/archotol.128.2.177
|View full text |Cite
|
Sign up to set email alerts
|

Near-Total Laryngectomy for Laryngeal Carcinomas With Subglottic Extension

Abstract: Success was directly related to adherence to precise indications in cancer surgery. While near-total laryngectomy is an effective and reliable treatment modality in laryngeal cancer surgery, its effectiveness in laryngeal cancers with subglottic extension is debatable. These subglottic lesions should be treated by total laryngectomy, which is a more radical surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
5

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
1
9
0
5
Order By: Relevance
“…The five-year survival rates for transglottic, supraglottic and subglottic cancers were 65.8, 53.8 and 20 per cent, respectively. 10 The presence of subglottic extension increased the risk of local and peristomal recurrence. Thakar et al also found inferior functional outcomes for near-total laryngectomy in cases with subglottic extension.…”
Section: Oncological Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…The five-year survival rates for transglottic, supraglottic and subglottic cancers were 65.8, 53.8 and 20 per cent, respectively. 10 The presence of subglottic extension increased the risk of local and peristomal recurrence. Thakar et al also found inferior functional outcomes for near-total laryngectomy in cases with subglottic extension.…”
Section: Oncological Safetymentioning
confidence: 99%
“…4,7,[10][11][12][13][14][15][16][17][18][19][20][21][22][23] CURRENT STATUS OF NEAR-TOTAL LARYNGECTOMY…”
Section: Oncological Safetyunclassified
“…In turn, this may influence prognosis and treatment decision‐making. For example, it has been suggested that use of organ preservation strategies such as radiotherapy or partial laryngectomy techniques may be less effective in T2 glottic tumours with subglottic spread, where more aggressive primary management such as total laryngectomy may produce better long‐term outcomes . Furthermore, use of an angled HR endoscope allows better visualisation of the anterior commissure and arytenoids, involvement of which again impacts on treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Bizim deneyimlerimize göre subglotik uzanımlarda nüks nedeniyle teknik kontrendikasyon sayılmalıdır. [85,86]…”
Section: Fonasyonda Dinamik şAnt Teknikleriunclassified